INVESTIGATION OF RCM-LIPI SURFACE ROUGHNESS COMPARISON RESULTS ON APMP.L-K8 - Ardi Rahman; Nurul Alfiyati; Rima Zuriah Amdani (Instrumentasi, 2018)
One way to assure the quality of measurement in calibration laboratories is to conduct inter-laboratory comparison with other laboratories those have a comparable scope. Research Center for Metrology (RCM-LIPI, previously KIM-LIPI) as the Indonesia’s national metrology institute (NMI) has followed and will continuously involve in international comparisons in various fields with other NMIs. In 2010, international comparison of surface roughness APMP.LK-8 was performed, where RCM-LIPI was one of the 10 participating laboratories from different countries those have outliers from a total of 16 participants. Outliers of RCM-LIPI data occurred in three of five artefacts, also noted that six participants did not perform measurements of soft-gauges. This paper discusses the results of the investigation on RCM-LIPI data in APMP.LK-8. There was an error of using of the calibration factor and error in determination of traced profile length. Verification of investigation results was carried out by re-measurement of three artifacts those were used in APMP.LK-8. Analysis of En value of RCM-LIPI against KCRV shows a decrease in outliers from 11 to 1 parameter i.e. Mr1. In addition, the methods of measurement soft-gauges using commercial software is also described.